The sources and the essence of the basque conflict in Spain - N. E. ANIKEEVA (Vestnik MGIMO-Universiteta)
THE SOURCES AND THE ESSENCE OF THE BASQUE CONFLICT IN SPAIN Today many states have to take into consideration the factor of terrorism while formulating their domestic policy. Spain is one of such states which had to deal with modern manifestation of the problem of terrorism in the history of its social development. In this connection it is necessary to analyze the sources and the essence of the basque conflict in Spain. By the basque conflict we mean that basque nationalists are carrying on struggle for winning complete independence from Spain both peacefully and using terror tactiсs.